Zgodovina ionske implantacije - Južnič, Stanislav (Vakuumist, 2000)
The article reviews the history of ion implantation. It concentrates on the time period from the invention of the ion implantation in 1905 until about 1978, when ion implaters have come of age. In the first part we describe the invention of ion implantation and development until World War II. In the second part of the article we review the development of the use of ion implantation for transistor industry after the World War II. We present the use of ion implantation in semiconductor devides. Special concern is put on the use of the ion implantation in metallury of recent times. Some details about echo of research of ion implantation among Slovenes are also described.
Keywords: ionska implantacija; zgodovinski pregledi; tranzistorji; fizika plazme